1999
DOI: 10.1016/s0002-9440(10)65191-7
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Soluble CD95 in Churg-Strauss Syndrome

Abstract: Deficiency of CD95 (Apo-1/Fas)-mediated apoptosis has recently been found in some autoimmune lymphoproliferative disorders due to inherited mutations of the CD95 gene. In this study , impairment of CD95 ligand-mediated killing of lymphocytes and eosinophils in Churg-Strauss Syndrome (CSS) , which was a result of variation of CD95 receptor isoform expression , is demonstrated. Compared to those from healthy individuals , peripheral blood lymphocytes from eight CSS patients exhibit a switch from the membrane-bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 26 publications
3
35
0
5
Order By: Relevance
“…The finding that CSS patients have a restricted HLA repertoire supports the hypothesis that only selected antigenic determinants may be involved in CSS, and simultaneously highlights the pathogenetic role of T cells. In accordance with this view, clonal T cell expansion has been demonstrated in CSS patients, and, because the T cell clones had similarly specific T cell receptors, they could recognize only a limited number of antigens (34). This finding, together with the present results, supports the notion that CSS is an antigen-driven disease.…”
Section: Discussionsupporting
confidence: 91%
“…The finding that CSS patients have a restricted HLA repertoire supports the hypothesis that only selected antigenic determinants may be involved in CSS, and simultaneously highlights the pathogenetic role of T cells. In accordance with this view, clonal T cell expansion has been demonstrated in CSS patients, and, because the T cell clones had similarly specific T cell receptors, they could recognize only a limited number of antigens (34). This finding, together with the present results, supports the notion that CSS is an antigen-driven disease.…”
Section: Discussionsupporting
confidence: 91%
“…15,48 Of these, interleukin-5 (which induces eosinophil production, activation, and surveillance) seems to play a critical role. 13 Other impaired apoptosis-related molecules (eg, soluble CD95, 49 tumor necrosis factor-related apoptosisinducing ligand receptor 3, 50 and discoidin domain receptor 51 ) may contribute to the delayed eosinophil clearance seen in CSS. Infiltrating eosinophils release cytotoxic enzymes (eg, major basic protein, 52 eosinophil peroxidase, 53 and eosinophilic cationic protein 54 ) and, ultimately, cause tissue injury.…”
Section: Role Of Effector T Cellsmentioning
confidence: 99%
“…In the article by Kain et al, 25 although neither epitope was homologous to MPO or PR3, the P 41-49 epitope was 100% homologous to amino acids 72 to 80 of the mature form of FimH, an adhesin located at the tip of type 1 fimbriae that is essential for the attachment of Gram-negative pathogens such as Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis to host epithelia. Reciprocal inhibition experiments showed that autoantibodies that recognized human LAMP-2, specifically its P [41][42][43][44][45][46][47][48][49] epitope, cross-reacted with FimH. Furthermore, rats immunized with recombinant FimH fusion protein developed antibodies to FimH that cross-reacted with human LAMP-2.…”
Section: Bacterial Antigens and Their Involvement In The Induction Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…These variations in splice isoform expression are likely to have functional consequences and have also been implicated as candidates for other autoimmune susceptibility loci (Evsyukova et al, 2010;Gillett et al, 2009;Muschen et al, 1999;Ueda et al, 2003). One of the strongest candidates of the SLAMF linked to lupus susceptibly in mice is Ly108 (CD352, SLAMF6).…”
Section: Slamf Spliced Variants and Their Role In Autoimmunitymentioning
confidence: 99%